Damnatio ad bestias: Performing Animality and Womanhood in Contemporary Irish and Galician Poetry (Altre Modernità, 2021)
The concomitant subjection of women and animals was denounced as early as 1990 by Carol J. Adams in The Sexual Politics of Meat, where she identified the intersections of discourses that aim at the subjugation of women and animals and censured those practices that animalize women and feminize animals for the better exploitation of both. More recent ecofeminist debates, however, have highlighted women’s vindication of animality with the aim to recuperate one’s repressed animal nature and rebel against oppressive anthropocentric and androcentric constrictions (Velasco Sesma 2017). This article focuses on contemporary Irish and Galician poetry concerned with the performativity of animality and womanhood in contemporary society and engaged in the emancipation of women and animals from patriarchal oppression. Ireland and Galicia have shared longstanding cultural bonds and, since the 1990s, have experienced a conspicuous accession of women writers who have participated in the feminist and environmental debates of their respective communities. This article exposes the intersecting discourses and practices that subdue animals and women, as evinced in contemporary Irish and Galician writing, and shows how poetry can become a locus of resistance and woman-animal complicity in the struggle for mutual emancipation.